Entropia de buracos negros em gravidade modificada - Gomes, Débora Aguiar (2023)
Despite the success of General Relativity, there are theoretical and experimental reasons which motivate the investigation of modifications of this theory. On the other hand, it is known that black holes have thermodynamic properties that are related to space-time geometry and, thus, are sensitive to corrections to General Relativity. In this work, we study the entropy of black holes in modified gravity. With that in mind, in the first part, we consider theories where the Lorentz symmetry is broken. Using the quantum tunneling method, we investigate the thermodynamic properties of black holes and how these are influenced by the violation of Lorentz symmetry. In the second part, we consider the Wald formalism that relates Noether currents due to diffeomorphisms to the entropy of black holes. Finally, we apply this formalism to teleparallel theories.